Beneficial Microbes in the Food Sector - Khoiroh Inda Dini; Natasya Zahra Aulia Putri; Sutrisno Adi Prayitno (Academic Letters, 2025)
Microorganisms play an essential role in modern food systems, extending beyond food spoilage to provide significant benefits in food processing, safety, and nutrition. Beneficial microbes such as bacteria, yeasts, and molds are widely used in fermentation to transform raw ingredients into value-added foods with improved flavor, texture, and shelf life. Through complex biochemical reactions, these microorganisms modify carbohydrates, proteins, and lipids, leading to the production of bioactive compounds and the reduction of anti-nutritional factors. Commonly used microbes include lactic acid bacteria, Saccharomyces cerevisiae, and molds such as Rhizopus and Aspergillus, which are involved in producing yogurt, cheese, bread, tempeh, and fermented vegetables. In addition to enhancing sensory qualities, microbial fermentation improves nutrient bioavailability and inhibits pathogenic microorganisms, thereby enhancing food safety. Regular consumption of fermented foods has also been associated with improved gut health and immune function. Overall, the controlled use of beneficial microbes represents a sustainable approach that integrates microbiology and food science to support food quality, public health, and food innovation.